IMPLEMENTASI DIVERSI DALAM PERKARA ANAK YANG BERKONFLIK DENGAN HUKUM DI KEPOLISIAN RESOR TANJUNG PINANG BERDASARKAN UNDANG- UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Indah Rahmasari; Emilda Firdaus; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In Article 1 Sub-Article 1 of Law Number 35 Year 2014 concerning Child Protection states that a Child is a person not yet 18 (eighteen) years of age, including a child still in the womb. The child is a person who must be kept his rights including in settling the case of children in conflict with the law. In solving the child's case in conflict with the law is done by way of diversion. Diversi is the transfer of the settlement of a Child case from a criminal justice process to proceedings outside the criminal court. This diversity is set forth in Article 1 number 7 of Law Number 11 Year 2012 on the Criminal Justice System of Children. The objectives of this thesis research are: Firstly, to know the implementation of diversi in case of conflict conflict with law at Tanjung Pinang Police Station based on Law Number 11 Year 2012 on Child Criminal Justice System, Second, to know the obstacle for Police to implement diversion in Children in conflict with the law at Tanjung Pinang Police Station based on Law Number 11 Year 2012 on Child Criminal Justice System, Third, To find out the effort to overcome obstacles for the Police in the implementation of the diversion in the case of children in conflict with the law at Tanjung Pinang Provincial Police Based on Law Number 11 Year 2012 on the Criminal Justice System of the Child.This type of research can be categorized in the type of sociological research. Because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted at Tanjung Pinang Resort Police, while the population and sample are all parties related to the problem studied in this research, the data source used is primary data, secondary data and tertiary data, data collection technique in this research with interview and study literature.From the results of research problems, there are 3 (three) points that can be inferred. Firstly, the implementation of the diversion at the Tanjung Pinang Police Force has been implemented, but it has not been working properly in accordance with Law Number 11 Year 2012 on the Criminal Justice System of the Child. Secondly, the obstacles faced by the Tanjung Pinang Police Force in implementing the diversi- sion in cases of children in conflict with the law, among others, the legal awareness of the community and the factors of law enforcement. Third, the efforts made by the Tanjung Pinang Police Force in facing obstacles to implementing diversion include socialization to the community and the addition of special investigator members of the child.Keywords: Implementation-Diversity-Children in Conflict with the Law